A Floricaula/Leafy gene homolog is preferentially expressed in developing female cones of the tropical pine Pinus caribaea var. caribaea - Dornelas,Marcelo Carnier (2005)
In angiosperms, flower formation is controlled by meristem identity genes, one of which, FLORICAULA (FLO)/LEAFY (LFY), plays a central role. It is not known if the formation of reproductive organs of pre-angiosperm species is similarly regulated. Here, we report the cloning of a conifer (Pinus caribaea var. caribaea) FLO/LFY homolog, named PcLFY. This gene has a large C-terminal region of high similarity to angiosperm FLO/LFY orthologs and shorter regions of local similarity. In contrast to angiosperms, conifers have two divergent genes resembling LFY. Gymnosperm FLO/LFY proteins constitute a separate clade, that can be divided into two divergent groups. Phylogenetic analysis of deduced protein sequences has shown that PcLFY belongs to the LFY-like clade. Northern hybridization analysis has revealed that PcLFY is preferentially expressed in developing female cones but not in developing male cones. This expression pattern was confirmed by in situ hybridization and is consistent with the hypothesis of PcLFY being involved in the determination of the female cone identity. Additionally, mutant complementation experiments have shown that the expression of the PcLFY coding region, driven by the Arabidopsis LFY promoter, can confer the wild-type phenotype to lfy-26 transgenic mutants, suggesting that both gymnosperm and angiosperm LFY homologs share the same biological role.